Protection Of Interest And Welfare Of Children Working In Malaysia Entertainment Industry: An Oybr\Riew - Nor Aida, Ab. Kadir; Naziree, Md Yusof (2017)
The concem regarding to children working in enterlainment industry in Malal,sia is infrequeutly discr.rssed. There are ceftain rights of this group of children that need to be saf'eguarded. They are exposed to exploitation if their interest and w'elfare are not protected. This writing seeks to study on law on r.vorking children in the entefiainment industry irt Malaysia for the purpose of examining the interest and rvelfare of the children are protected and safeguarded. Therefore, it rvi[[ analyse the various lau,s that relates to the above tnatters includitrg the international instrurlents in which Mala,vsia is a signator)' pafiy. Besides, this arlicle also aims to identify rvhether there is any rights of tlie children that might be violated rvhen they act as an actor or performer in the entefiaintnent industry. [f violation of their rights truly happens. what are the appropriate steps to be taken in evading any harm to the children working in entertainment industry? This is to make sure the "best interest'principle is upheld fbr children in Malaysia. This r.vriting is a qualitative study on emplovment larv and the rights of child in Malaysia, rvhich mainly based on library research.